Histopathological findings in the uteri and ovaries of clinically healthy cats presented for routine spaying. Issue 8 (August 2021) - Binder, Claudia; Reifinger, Martin; Aurich, Jörg; Aurich, Christine
Objectives: The aim of this study was to assess the histopathological findings in the uteri and ovaries from clinically healthy queens presented for elective spaying. Methods: Ovaries and distal uterine horns or complete uteri from 106 female cats were evaluated for pathological alterations. Results: Pathological alterations of the uterus and/or ovaries were evident in 29 cats; of these, corpora lutea were present on the ovaries of 15 cats. Ovarian cysts were found in 15 cats and were classified as cysts of the Wolffian or Muellerian ducts (n = 4), follicular cysts (n = 4), luteal cysts (n = 1), cystic rete ovarii (n = 2), combinations of different cysts (n = 2) and non-classifiable cysts (n = 2). In 21/106 cats, cystic endometrial hyperplasia (CEH) was present. The incidence of CEH increased with the age of the cat. Six cats had purulent endometritis with or without distension of the uterine lumen. Hyperplastic lesions of the endometrium were detected in two cats. In one cat, a uterine horn malformation with duplication of one uterine horn lumen was diagnosed. Conclusions and relevance: Whereas the majority of ovarian cysts and slight-to-moderate CEH are unlikely to interfere with an animal's wellbeing, endometritis must be considered a serious health problem that requires veterinary attention.